IMPLEMENTATION OF THE MUSYARAKAH MUTANAQISAH AKAD PERSPECTIVE OF JURISPRUDENCE IN PT BPR SYARIAH NTB - Mansyur, Mansyur; Aciria, Siti (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
This research examines the implementation of the musyarakah mutanaqisah contract from the perspective of muamalah fiqh at PT BPR Syariah Dinar Ashri NTB. This research departs from public attention to Islamic banking in NTB. PT BPR Syariah Dinar Ashri NTB is one of the Islamic financial institutions that has tried to implement sharia values on the musyarakah mutanaqisah contract through continuous innovation and evaluation in accordance with sharia operational standards and regulations of the Financial Services Authority of the Republic of Indonesia. This research uses qualitative research methods. Data were collected through interviews with stake holders of PT BPR Syariah Dinar Ashri NTB, interviews with the sharia supervisory board, review of financial services authority regulations, review of DSN-MUI fatwas and analysis of related data and documents. The results of the study show that in applying the musyarakah mutanaqisah contract, this institution collaborates in asset ownership (musyarakah contract), customers have other objects as rental objects (ijarah contract) and bai' contracts on musyarakah objects. As for its application, there are still shortcomings in it, such as in the contract system and contract implementation. In applying Islamic values such as the principles of justice, transparency, avoiding usury, gharar and maisir, PT BPR Syariah Dinar Ashri NTB provides responsibility and provides legal protection for the parties